Comparative study of realistic ship motion simulation for optimal ship routing of a bulk carrier in rough seas. (15th September 2022) - Waskito, Kurniawan T.; Sasa, Kenji; Chen, Chen; Kitagawa, Yasushi; Lee, Sang-Won
Abstract: Accurate estimation of ship motions is inevitable for safe, economical, and environmentally friendly ship routing. Onboard measurements have been conducted for a bulk carrier in 2010–2016, including eight rough seas in the Northern and Southern Hemispheres. Rough sea conditions were reproduced using a wave model, WaveWATCH III, with wind inputs from meteorological organizations. Ship performances were evaluated using traditional seakeeping theories, with the main focus being on transverse motion. The 3D frequency-domain Rankine Panel Method (RPM), New Strip Method (NSM), and Enhanced Unified Theory (EUT) were compared. First, roll decay tests and simplified Ikeda's methods of roll damping were applied in each method. Second, the results of the model tests in oblique seas in regular waves were additionally considered for the accurate estimation of ship motions in actual seas. These were validated with measured ship motions in eight rough sea voyages. It was found that errors are smaller in the RPM than those in the EUT and NSM for measured roll and pitch motions in actual seas. The favorable results obtained using the proposed methods may provide a new alternative for optimal ship routing to predict ship roll and pitch motions in rough seas with reliable accuracy and computational efficiency. Highlights: Ship motions in actual seas are analyzed for 28, 000DWT bulk carrier. Frequency-domain Rankine panel method is used to estimate ship motions. New strip method and enhanced unified theory are used for comparison. Roll damping is estimated by decay tests and simplified Ikeda's methods. Ship motion computations are validated by model tests and actual seas.